PENGARUH KUALITAS PELAYANAN DAN EKUITAS MEREK TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN PADA PT. GLOBAL INTI AGRO DI KOTA PEKANBARU - Syawalmi, Laily; Zulkarnain, Zulkarnain; Samsir, Samsir (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to analyze the effect of Service Quality and BrandEquity on customer satisfaction. To analyze the effect of Service Quality andBrand Equity on Consumer loyalty To analyze the influence of customersatisfaction on consumer loyalty PT. Global Core Agro in Pekanbaru City.The research population is farmers as much as 670 people and retailers405 people, so in 2016 as many as 1,075 consumers at PT. Global Inti Agro inPekanbaru City. The sample size that will be used is 136 people. Data analysisusing WarpPLS approach. WarpPLS is one of the variance-based SEM statisticalmethods designed to solve multiple regressions when specific data problemsoccur, such as very small sample size, missing values and multicollinearity.WarpPLS is an alternative approach that shifts from a Covarian-based SEMapproach to a variance-based.The results of this study indicate that the better the quality of service, itcan provide satisfaction to consumers and ultimately can increase the number ofconsumers. The better the brand equity can provide satisfaction to customersatisfaction and ultimately the number of consumers will increase. The better thequality of services provided will certainly make consumers become loyal, with thebetter the service provided will certainly increase customer satisfaction andimpact on customer loyalty to the company. The better the brand equity accordingto the given consumer will certainly make the consumer become very confidenttowards the company, with the advent of trust in the company will certainlyincrease customer loyalty to the company. The higher satisfaction obtained byconsumers to make consumers more satisfied, so with the satisfaction ofconsumers will increase customer loyalty to the company.